Posted by **Richard** on Friday, November 3, 2006 at 1:26pm.

Am I going in the right track?

8x -1/x + 5x - 3/2x

= 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2

16x^2 - 2x + 5x^2 - 3x/2x^2

=21x^2 - 5/2x^2

Find the LCD

6/7z- 28, 8/x^2 -4x

= 7x(x-4)

Simplify

3x^2 - 2x/15x-10

= x/5

Let's start by looking at your first problem:

8x -1/x + 5x - 3/2x

To simplify, use a common denominator, which is 2x.

16x^2/2x - 2/2x + 10x^2/2x - 3/2x

Now we have:

(16x^2 - 2 + 10x^2 - 3)/2x

Combining like terms in the numerator:

(26x^2 - 5)/2x

And that's as far as we can go on this one.

Is your second problem supposed to be 6/(7x - 28), 8/(x^2 - 4x)?

If so, your LCD is correct!

For your third problem, I'm going to assume it is this:

(3x^2 - 2x)/(15x - 10)

If so, your answer is correct!

If your first problem was this:

(8x - 1)/x + (5x - 3)/2x

...then your answer is close. The common denominator would still be 2x, but the answer would be (21x - 5)/2x instead.

I hope this helps.

## Answer This Question

## Related Questions

- Algerbra - how do you solve 7(3x+4)=8(2x+5)+13 expand the parenthesis...I will ...
- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- algerbra - 7(3x+4)=8(2x+5)+13 how would I start a equation like this would it be...
- algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...
- Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...
- algerbra 1 - 5x+8+3x-x+5=6x-3 do I start like this 5x+3x-x or 5x+3x+8+5=6x-3 I ...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- math - please help - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - ...
- math - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4...

More Related Questions